2017
DOI: 10.4238/gmr16019166
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-139 modulates Alzheimer’s-associated pathogenesis in SAMP8 mice by targeting cannabinoid receptor type 2

Abstract: ABSTRACT. Alzheimer's disease (AD) is a neurodegenerative disorder, and is the most common type of dementia in the elderly population. Growing evidence indicates that microRNAs (miRNAs) play a crucial role in neuroinflammation associated with AD progression. In this study, we analyzed the expression of microRNA-139 (miR-139) as well as the learning and memory function in AD. We observed that the miR-139 expression was significantly higher in the hippocampus of aged senescence accelerated mouse prone 8 (SAMP8) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…CB1R mRNA and protein levels were significantly reduced in cardiac cells transiently transfected with pre-miR-494. Additionally, miR-139 was shown to impair the hippocampus-dependent learning and memory functions by targeting CB2R in an accelerated-aging animal model [40]. Immunohistochemical analysis showed that overexpression of miR-139 resulted in a decrease in the number of CB2R-positive nuclei in the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…CB1R mRNA and protein levels were significantly reduced in cardiac cells transiently transfected with pre-miR-494. Additionally, miR-139 was shown to impair the hippocampus-dependent learning and memory functions by targeting CB2R in an accelerated-aging animal model [40]. Immunohistochemical analysis showed that overexpression of miR-139 resulted in a decrease in the number of CB2R-positive nuclei in the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…Some miRNAs like miR-139 over express in AD, this overexpression impairs the hippocampus-dependent learning and memory formation by targeting the cannabinoid receptor type 2 (Tang et al, 2017 ), a membrane marker of activated microglial cells, which triggers pathophysiological events involved in synaptic plasticity and neuroprotection but is also implicated in diverse roles in regulating memory, depending on memory types and brain areas (Li and Kim, 2016 ).…”
Section: Alzheimer’s Diseasementioning
confidence: 99%
“…In addition to the markers specifically identified as AD signatures, many studies evidenced that the levels of a variety of miRNAs are altered in the circulating exosomes of AD patients [46,268]. For example, miR-139 is overexpressed in AD, and its increase reduces the expression of the cannabinoid receptor type 2 (CB2) [247]. CB2 is a membrane protein present on activated microglial cells and involved in synaptic plasticity, and in the regulation of memory formation as well [269].…”
Section: Evs In Neuropathologymentioning
confidence: 99%